Sustained Action of Ceramide on the Insulin Signaling Pathway in Muscle Cells: IMPLICATION OF THE DOUBLE-STRANDED RNA-ACTIVATED PROTEIN KINASE - Hage Hassan, Rima; Pacheco de Sousa, Ana Catarina; Mahfouz, Rana; Hainault, Isabelle; Blachnio-Zabielska, Agnieszka; Bourron, Olivier; Koskas, Fabien; Górski, Jan; Ferré, Pascal; Foufelle, Fabienne; Hajduch, Eric (The Journal of biological chemistry, 2016)
In vivo, ectopic accumulation of fatty acids in muscles leads to alterations in insulin signaling at both the IRS1 and Akt steps. However, in vitro treatments with saturated fatty acids or their derivative ceramide demonstrate an effect only at the Akt step. In this study, we adapted our experimental procedures to mimic the in vivo situation and show that the double-stranded RNA-dependent protein kinase (PKR) is involved in the long-term effects of saturated fatty acids on IRS1. C2C12 or human muscle cells were incubated with palmitate or directly with ceramide for short or long periods, and insulin signaling pathway activity was evaluated. PKR involvement was assessed through pharmacological and genetic studies. Short-term treatments of myotubes with palmitate, a ceramide precursor, or directly with ceramide induce an inhibition of Akt, whereas prolonged periods of treatment show an additive inhibition of insulin signaling through increased IRS1 serine 307 phosphorylation. PKR mRNA, protein, and phosphorylation are increased in insulin-resistant muscles. When PKR activity is reduced (siRNA or a pharmacological inhibitor), serine phosphorylation of IRS1 is reduced, and insulin-induced phosphorylation of Akt is improved. Finally, we show that JNK mediates ceramide-activated PKR inhibitory action on IRS1. Together, in the long term, our results show that ceramide acts at two distinct levels of the insulin signaling pathway (IRS1 and Akt). PKR, which is induced by both inflammation signals and ceramide, could play a major role in the development of insulin resistance in muscle cells.